2007
DOI: 10.1038/sj.cgt.7701019
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of products of genes to tumor sites using adoptively transferred A-NK and T-LAK cells

Abstract: Despite successes in animals, cytokine gene expression selectively in human tumors is difficult to achieve owing to lack of efficient delivery methods. Since interleukin (IL)-2-activated natural killer (A-NK) and phytohemagglutinin and IL-2 activated killer T (T-LAK) cells, as previously demonstrated, localize and accumulate in murine lung tumor metastases following adoptive transfer, we transduced them to test their ability to deliver products of genes selectively to tumors. Assessments of transduction effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…5C and 5E). These results were consistent with previous observations: NK cells not only accumulate selectively at tumor sites independent of tumor antigen expression, but also penetrate deeply into tumor tissues (1013). Upon activation, infiltrated NK cells proliferate and upregulate effector molecules such as perforin, granzymes, FasL, TNF-α, and TRAIL (2427).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…5C and 5E). These results were consistent with previous observations: NK cells not only accumulate selectively at tumor sites independent of tumor antigen expression, but also penetrate deeply into tumor tissues (1013). Upon activation, infiltrated NK cells proliferate and upregulate effector molecules such as perforin, granzymes, FasL, TNF-α, and TRAIL (2427).…”
Section: Discussionsupporting
confidence: 94%
“…Several researchers have reported that NK cells possess tumor-infiltrating capability and accumulate selectively at tumor sites (1013). First, we investigated whether NK-92MI or NK-92MI-FETZ cells can migrate to cancer cells in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A-NK cells pretreated with IL-12 or A-NK cells capable of IL-12–autostimulation via transgene IL-12 production need only 1/10–1/100 of the amount of IL-2 needed to maintain the same viability and functionality as A-NK cells that have not been stimulated with IL-12. 57 This is likely due to the IL-12–induced expression of the IL-2 receptor alpha chain by the A-NK cells, enabling them to express the complete IL-2α-β-γ, high-affinity IL-2 receptor. Thus, by adoptive transfer of IL-12 transduced A-NK cells supported by just two injections of Peg–IL-2 (each of 3 × 10 4 IU) given on the same day as the A-NK cells, a significant prolongation of survival was observed in both 3-day and well-established 7-day models of B16 and MCA205 lung metastases.…”
Section: In Vivo Function Of A-nk Cells Is Highly Dependent On Cytmentioning
confidence: 99%
“…Thus, by adoptive transfer of IL-12 transduced A-NK cells supported by just two injections of Peg–IL-2 (each of 3 × 10 4 IU) given on the same day as the A-NK cells, a significant prolongation of survival was observed in both 3-day and well-established 7-day models of B16 and MCA205 lung metastases. 57,58 Although the A-NK-cell–produced IL-12 undoubtedly supported anti-tumor responses in addition to those generated by non–IL-12–producing A-NK cells, tumor homing by A-NK cells remained a very important and critical factor for the anti-tumor effect achieved by the IL-12 gene-transduced A-NK cells. 58 …”
Section: In Vivo Function Of A-nk Cells Is Highly Dependent On Cytmentioning
confidence: 99%